Art and Perception: Using Empirical Aesthetics in Research on Consciousness - Ansorge, Ulrich; Pelowski, Matthew; Quigley, Cliodhna; Peschl, Markus F.; Leder, Helmut (Frontiers in Psychology, 2022)
Understanding consciousness is a major frontier in the natural sciences. However, given the nuanced and ambiguous sets of conditions regarding how and when consciousness appears to manifest, it is also one of the most elusive topics for investigation. In this context, we argue that research in empirical aesthetics—specifically on the experience of art—holds strong potential for this research area. We suggest that empirical aesthetics of art provides a more exhaustive description of conscious perception than standard laboratory studies or investigations of the less artificial, more ecological perceptual conditions that dominate this research, leading to novel and better suited designs for natural science research on consciousness. Specifically, we discuss whether empirical aesthetics of art could be used for a more adequate picture of an observer’s attributions in the context of conscious perception. We point out that attributions in the course of conscious perception to (distal) objects versus to media (proximal objects) as origins of the contents of consciousness are typically swift and automatic. However, unconventional or novel object-media relations used in art can bring these attributions to the foreground of the observer’s conscious reflection. This is the reason that art may be ideally suited to study human attributions in conscious perception compared to protocols dedicated only to the most common and conventional perceptual abilities observed under standard laboratory or “natural”/ecological conditions alone. We also conclude that art provides an enormous stock of such unconventional and novel object-media relations, allowing more systematic falsification of tentative conclusions about conscious perception versus research protocols covering more conventional (ecological) perception only. We end with an outline of how this research could be carried out in general.